The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1242/jcs.243519
|View full text |Cite
|
Sign up to set email alerts
|

Squaring the EMC – how promoting membrane protein biogenesis impacts cellular functions and organismal homeostasis

Abstract: Integral membrane proteins play key functional roles at organelles and the plasma membrane, necessitating their efficient and accurate biogenesis to ensure appropriate targeting and activity. The endoplasmic reticulum membrane protein complex (EMC) has recently emerged as an important eukaryotic complex for biogenesis of integral membrane proteins by promoting insertion and stability of atypical and sub-optimal transmembrane domains (TMDs). Although confirmed as a bona fide complex almost a decade ago, light i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
49
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(53 citation statements)
references
References 103 publications
(203 reference statements)
3
49
1
Order By: Relevance
“…For example, the initial identification of the EMC included numerous genetic interactions with both protein and lipid synthesis factors in yeast ( Jonikas et al, 2009 ) and these disparate interdependencies have been subsequently observed in numerous species including human EMC ( Lahiri et al, 2014 ; Tang et al, 2017 ; Guna et al, 2018 ; Volkmar et al, 2019 ; Volkmar and Christianson, 2020 ). Also, several client proteins are enzymes or cofactors involved in multiple stages of lipid synthesis or trafficking, and this may provide a unifying explanation for the range of genetic interactions and co-essentiality observations reported to date ( Guna et al, 2018 ; Shurtleff et al, 2018 ; Volkmar et al, 2019 ; Tian et al, 2019 ; Wainberg et al, 2019 ; Corradi et al, 2019 ; Volkmar and Christianson, 2020 ). Perhaps by facilitating the insertion of sterol synthesis protein SQS, the EMC allows for modulation of local membrane thickness and lipid composition to accommodate differences within the broad range of membrane proteins being synthesized.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the initial identification of the EMC included numerous genetic interactions with both protein and lipid synthesis factors in yeast ( Jonikas et al, 2009 ) and these disparate interdependencies have been subsequently observed in numerous species including human EMC ( Lahiri et al, 2014 ; Tang et al, 2017 ; Guna et al, 2018 ; Volkmar et al, 2019 ; Volkmar and Christianson, 2020 ). Also, several client proteins are enzymes or cofactors involved in multiple stages of lipid synthesis or trafficking, and this may provide a unifying explanation for the range of genetic interactions and co-essentiality observations reported to date ( Guna et al, 2018 ; Shurtleff et al, 2018 ; Volkmar et al, 2019 ; Tian et al, 2019 ; Wainberg et al, 2019 ; Corradi et al, 2019 ; Volkmar and Christianson, 2020 ). Perhaps by facilitating the insertion of sterol synthesis protein SQS, the EMC allows for modulation of local membrane thickness and lipid composition to accommodate differences within the broad range of membrane proteins being synthesized.…”
Section: Discussionmentioning
confidence: 99%
“…In Saccharomyces cerevisiae , EMC8 has been lost (Wideman, 2015). Only EMC3 displays clear homology to other membrane protein insertases, the Oxa1 family (Wideman, 2015; Volkmar & Christianson, 2020). This family includes YidC, which inserts TMDs into the bacterial cytoplasmic membrane, usually in cooperation with the Sec61‐homologous SecYEG channel (Volkmar & Christianson, 2020).…”
Section: Figure Comparison Of the Structures Of Human And Yeast Emcmentioning
confidence: 99%
“…Only EMC3 displays clear homology to other membrane protein insertases, the Oxa1 family (Wideman, 2015; Volkmar & Christianson, 2020). This family includes YidC, which inserts TMDs into the bacterial cytoplasmic membrane, usually in cooperation with the Sec61‐homologous SecYEG channel (Volkmar & Christianson, 2020). Their association, along with the SecDF ancillary complex, forms a holo‐translocon capable of protein secretion and TMD insertion, with striking similarities to the EMC complex (Martin et al , 2019).…”
Section: Figure Comparison Of the Structures Of Human And Yeast Emcmentioning
confidence: 99%
“…Aside from its well-described function in membrane protein insertion and assembly (Dalbey and Kuhn, 2014), YidC is required for folding of the polytopic membrane proteins LacY and MalF (Nagamori et al, 2004;Serdiuk et al, 2016;Serdiuk et al, 2019;Wagner et al, 2008;Zhu et al, 2013). Our model for the Shr3 chaperone function in the biogenesis of AAP is analogous to that of YidC in the folding of LacY where hydrophobic interactions mediate shielding of LacY, providing a protective chamber that reduces energetically unfavorable contacts in the non-native structure during translation (Zhu et al, 2013) More recently, the conserved eukaryotic ER membrane protein complex (EMC) has been implicated in various roles facilitating membrane protein biogenesis (Volkmar and Christianson, 2020), including those of a MS insertase (Chitwood et al, 2018;Guna et al, 2018) and a chaperone-like capacity for diverse polytopic membrane proteins (Shurtleff et al, 2018). Although mechanistic details of how the EMC exerts its chaperone-like function remain to be elucidated, it apparently acts in close proximity with nascent polytopic membrane proteins typically enriched for MS containing polar or charged residues (Shurtleff et al, 2018).…”
Section: Discussionmentioning
confidence: 95%